21st century urban race politics representing minorities as universal interests - Perry, Ravi K. (Bingley, U.K. : Emerald, 2013)
21st Century Urban Race Politics begins by offering a twenty-first-century understanding of minority representation in historically majority-Caucasian cities and draws on case studies in cities throughout the United States. The aim of this volume is to take stock of what we know about the advantages and disadvantages of the "racialized" and "deracialized" approaches to governance and to describe a third approach, the "universalized interest approach." The authors argue that minority elected officials, when given the power and resources to do so, often do more than represent constituent interests without acknowledging the representation of members of their racial/ethnic group in urban communities. Contributors describe how mayors of various backgrounds have sought to represent minority interests in electoral and governing contexts. In each case, the mayors are found to represent minority interests. In most cases, the representation of minority interests is accomplished without deemphasizing the significance of race and as the mayor maintains support from whites within their electoral and governing coalitions. With case studies from across the country, in medium-sized and large cities, and mayors of various backgrounds, the volume provides a vivid account of how different minority mayors have handled minority representation in historically majority Caucasian cities and what lessons academics and politicians can learn from them.
ch. 1. Political transformation in providence : the election of Mayor Angel Taveras / Marion Orr, Carrie Nordlund -- ch. 2. constructing a moderate multiracial coalition in "America's most diverse city" : Kevin Johnson and Coalition Politics in Sacramento / Corey Cook -- ch. 3. Beyond booker : assessing the prospects of black and Latino mayoral contenders in Newark, New Jersey / Andra Gillespie -- ch. 4. "Showing his color" : Mark Mallory's racial distinctiveness as seen through media representations / Harwood K. McClerking -- ch. 5. Asian American politics in Oakland : the rise of Mayor Jean Quan / Kim Geron -- ch. 6. The mile high difference : examining the impact of political and institutional context on the electoral strategies pursued by minority mayors in Denver, and the impacts of those strategies on minority communities / Davin L. Phoenix -- ch. 7. Michael Coleman : the Midwestern middleman / Stefanie Chambers, Will Schreiber-Stainthorp -- ch. 8. Antonio Villaraigosa, Los Angeles, and the politics of race / Boris E. Ricks -- ch. 9. Balancing act : racial empowerment and the dual expectations of Jack Ford in Toledo, Ohio / Ravi K. Perry, Andrea Owens-Jones -- ch. 10. "The last black mayor of Atlanta?" / Todd C. Shaw ... [et al.] -- ch. 11. The election of the first African American female mayor in Georgia's first city : the long struggle for African American empowerment in Savannah / Pearl K. Ford Dowe, Hanes Walton -- ch. 12. Buffalo, New York : a discussion of Mayor Brown's leadership / Zulema Blair -- ch. 13. From Fenty to Gray : the salience of urban gentrification, black politics, and substantive representation in Washington, DC's 2010 mayoral elections / Menna Demessie, Andra Gillespie -- Epilogue : future prospects for targeted universalism / Ravi K. Perry.
Keywords: Social Science -- Ethnic Studies -- General; Social Science -- Discrimination & Race Relations; Social Science -- General; Ethnic minorities & multicultural studies; Ethnic studies; Minorities -- Political activity -- United States; United States -- Race relations -- Political aspects -- History -- 21st century; United States -- Politics and government -- 21st century